Trigonometric equation

4tanx-1 = - 3tan(-x)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You want to solve 4 tan x - 1 = - 3*tan(-x)

Now tan -x = - tan x

4 tan x - 1 = - 3*tan(-x)

=> 4*tan x - 1 = 3* tan x

=> tan x = 1

=> x = arc tan 1

=> x = pi/4 + n*pi and 5*pi/4

For the equation x = pi/4 + n*pi and x = 5*pi/4 + n*pi

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial